Predicting the Salt Water Intrusion in the Shatt al-Arab Estuary using an Analytical Approach - Abdullah, Ali D.; Gisen, J. I. A.; Pieter, van der Zaag; Hubert H. G., Savenije; Usama F. A., Karim; Ilyas, Masih; Ioana, Popescu (European Geosciences Union, 2016)
Longitudinal and vertical salinity measurements are used in this study to predict the extent of inland seawater intrusion in a deltaic river estuary. A predictive model is constructed to apply to the specific tidal, seasonal, and discharge variability and geometric characteristics of the Shatt al-Arab River (SAR) situated along the border of Iraq and Iran. Reliable hydrologic simulation of salinity dynamics and seawater intrusion was lacking prior to this study. Tidal excursion is simulated analytically using a 1-D analytical salt intrusion model with recently updated equations for tidal mixing. The model was applied under different river conditions to analyse the seasonal variability of salinity distribution during wet and dry periods near spring and neap tides between March 2014 and January 2015. A good fit is possible with this model between computed and observed salinity distribution. Estimating water abstractions along the estuary improves the performance of the equations, especially at low flows and with a well-calibrated dispersion–excursion relationship of the updated equations. Salt intrusion lengths given the current data varied from 38 to 65 km during the year of observation. With extremely low river discharge, which is highly likely there, we predict a much further distance of 92 km. These new predictions demonstrate that the SAR, already plagued with extreme salinity, may face deteriorating water quality levels in the near future, requiring prompt interventions.